1970
DOI: 10.1002/1097-0142(197004)25:4<896::aid-cncr2820250423>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Hemangiopericytoma.Report of a case and comprehensive review of the literature

Abstract: A case of recurrent and metastatic hemangiopericytoma of the left thigh is presented. The following conclusions as to clinical and pathologic features, with special reference to the malignant potential and recurrence rate of this tumor, and the results of various forms of treatment have been drawn from a comprehensive review of 224 cases collected from the literature: 1. Hemangiopericytoma is highly malignant over a lifetime in about 50% of all cases treated; 2. The recurrence rate varies with the particular o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0
6

Year Published

1973
1973
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(72 citation statements)
references
References 64 publications
1
65
0
6
Order By: Relevance
“…9 According to our review of the literature, total recurrence rates, including local and distant, range from 19% to 52%. 3,4 The most common metastatic sites by the hematogenous route are the lungs, liver, and bone. 4 Recurrence may occur after a prolonged disease-free interval, which stresses the need for long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 According to our review of the literature, total recurrence rates, including local and distant, range from 19% to 52%. 3,4 The most common metastatic sites by the hematogenous route are the lungs, liver, and bone. 4 Recurrence may occur after a prolonged disease-free interval, which stresses the need for long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…However, local recurrences or distant metastases develop in about 19%-52% of patients. 3,4 Although the role of radiotherapy and chemotherapy is still not well established, we recently treated a patient with malignant dominal wall and around the bilateral iliac arteries (Fig. 1d).…”
Section: Introductionmentioning
confidence: 99%
“…5 The majority of these tumors are of the acquired type and tend to be highly malignant. 10 In contrast, CHP is extremely rare, comprising only 3.3%-7.0% of all HPs. 11 In a large series of pediatric neoplasms, only 2.6% were congenital, and 3.0% of these were HPs.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Although most cases of CHP follow a benign clinical course with the possibility of a spontaneous regression, a complete surgical resection with a sufficient margin, whenever possible, remains the treatment of choice. 5,7,9,16 Metastases or local recurrence may occur after several years of disease-free intervals, 10 and therefore, close and long-term follow-up of the patient is necessary. 9,16 In cases where recurrence or metastasis does occur, chemotherapy has been used with varying degrees of success; however, the role of radiation therapy in these tumors continues to be controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Review of a representative slide ofthe original lesion confirmed this. We were fortunate to trace a slide ofthe 1961 lesion which showed a haemangiopericytoma with a mitotic rate of [1][2] association with hypoglycaemia has been reported5. The peak incidence of the tumours is in the 40-60 age group, but cases have been reported in patients of all ages.…”
mentioning
confidence: 91%